Effect of sectioning, drying, and shading on the propagation of Opuntia cochenillifera (L.) Mill. cladodes - Llinás , Rafael; Atencio, Carlos; González, Andy; Rivero, Gisela; Ortega , Jorge; Colmenares, Ciolys; León, Ruben (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2026)
Opuntia cochenillifera (L.) Mill. has a forage potential in arid areas. Because pastures are insufficient to meet livestock’s nutritional demands during the dry season, this research aimed to evaluate the effects of sectioning (S), drying (D), and shading (Sh) of cladodes on the propagation of Opuntia cochenillifera (L.) Mill. The S factors (whole cladode and apical, middle, and basal sections), D (pre-drying at room temperature on mesh under shade for 14 days), and Sh (with and without shading under 80 % density raffia mesh), resulted in a combination of 16 treatments, arranged in a split-plot treatment design and a completely randomized experimental design. Percentages of living, rooted, and sprouted cladodes, number of shoots per cladode, and number and length of roots were evaluated 35 days after establishment. An analysis of variance and a means test were applied to determine differences among treatments. An increase in the percentage of rooted cladodes was obtained with the middle, apical, and basal fractions compared to the whole cladode, regardless of the drying process. Prior shading was counterproductive for cladode survival; high environmental humidity, combined with their water content, may have favored the appearance of secondary rots. In general, considering most of the variables evaluated, cladode sectioning without drying emerged as the best technique for asexual propagation of the species, due to the yield of vegetative material and its practicality.